Experimental study of Otitis media with Pseudomonas aerugenonsa in mice and treated with alcoholic cold extract of dandelion compared with used of otucalm drops and Lactobacillus acidophilus - Al-khafaji, Narjis A. (The Iraqi Journal of Veterinary Medicine, 2013)
This study has revealed the importance of natural herbal products to control antibiotics resistant bacteria which are being a threat to human and animal health and focused on antibacterial potential of aqueous infusion of Dandelion alcoholic cold extract against Pseudomonas aeruginosa. The experimental studies include (18) healthy mice were randomly divided in to 6 equal groups, all 5thgroup injected with P. aerugenosa 106CFU/ ml (0.05 ml) except 6th group which injected with phosphate buffer saline (control negative). 1st group killed after 48hr of injection, 2nd group treated with otucalm, 3rd treated with Dandelion cold alcoholic extract, 4th group treated with Dandelion locally and lactobacillus acidophilus orally, 5th group injected with bacteria (control positive) andkilled after the end of the experiment. The result showed that the 4th group was the best group show the highly sensitive effect in vitro and no clear pathological lesion and increase the immunity and health of animal in vivo compare with other groups. Dandelion showed nontoxic effect and noncombination with other drugs and significantly increased the ability of P. aerugenosa isolated from otitis media it’s more pathogenic than bacteria isolated from others organs in the same animals.